2015
DOI: 10.1111/cobi.12608
|View full text |Cite
|
Sign up to set email alerts
|

Constraints of philanthropy on determining the distribution of biodiversity conservation funding

Abstract: Caught between ongoing habitat destruction and funding shortfalls, conservation organizations are using systematic planning approaches to identify places that offer the highest biodiversity return per dollar invested. However, available tools do not account for the landscape of funding for conservation or quantify the constraints this landscape imposes on conservation outcomes. Using state-level data on philanthropic giving to and investments in land conservation by a large nonprofit organization, we applied l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 47 publications
(108 reference statements)
0
26
0
Order By: Relevance
“…Some forms of philanthropy involve sustainable funding through endowments, while others provide finite funding. There is always a risk that the aspirations of philanthropic funders do not meet national conservation priorities (Larson et al 2016), perhaps reflecting the wishes of the funder. There is also the perceived or real risk that philanthropic investors will use their influence to impose future obligations on central government funding.…”
Section: Restoration Fundingmentioning
confidence: 99%
“…Some forms of philanthropy involve sustainable funding through endowments, while others provide finite funding. There is always a risk that the aspirations of philanthropic funders do not meet national conservation priorities (Larson et al 2016), perhaps reflecting the wishes of the funder. There is also the perceived or real risk that philanthropic investors will use their influence to impose future obligations on central government funding.…”
Section: Restoration Fundingmentioning
confidence: 99%
“…Another study has shown that investments are better explained by species richness than land cost (Fishburn et al 2013). Areas where conservation efforts are invested are strongly correlated with amounts of funds raised locally, despite large predicted gains from reallocating a portion of this funding across space (Larson et al 2016). By contrast, donations to TNC were highest around major metropolitan areas where there are fewer opportunities to spend the money locally (Fovargue et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Broadly speaking, academic literature on funding for conservation oscillates between focussing on efficiency on the one hand (Armsworth et al 2012;Bennett et al 2015;Bos et al 2015;Larson et al 2016;Miller et al 2013) and taking a critical stance on conservation networks on the other hand (BĂŒscher et al 2014;Corson 2010;Kay 2018). The efficiency-focussed literature is primarily concerned with optimising funding, for example by looking into the efficiency of conservation organisations, the workings of financial mechanisms or the institutional and local contexts within which conservation occurs.…”
Section: Introductionmentioning
confidence: 99%